THE EFFECT OF UNUSUAL MOVINGACTIVITY ANNOUNCEMENT ON STOCK RETURN AND TRADING VOLUME IN INDONESIA STOCK EXCHANGE - Ika Yanuarti; Mulyono Mulyono (STIE Perbanas Surabaya, 2013)
One of the information submitted by the Indonesia Stock Exchange, related to stock trading is theannouncement of Unusual Market Activity (UMA). The UMA announcement is a trade activitiesand or price movements of unusual effect on a certain period of time which, according to the assessment on the Indonesia Stock Exchange could potentially disrupt the holding of regular stocktrading, fair and efficient. This announcement does not necessarily indicate a breach in the fieldof capital market. Publication ofUMA announcement can be one form of protection to investorswhen a company's stock price has been moreover volatile. The sample of this study is the listedcompanies included in UMA announcement period 2011. This study uses Paired Samples T-testAnalysis and Wilcoxon Signed Ranks Test. The conclusion is the stock return was affected byUMA announcement but the trading volume activity was not affected by UMA announcement.